Phytochemical and bioactivity evaluation of Etlingera coccinea (Blume) S. Sakai and Nagam collected from six different locations in Sabah - Jacqueline Vincent (2011)
Etlingera coccinea (Blume) 5. Sakai and Nagam is a member of Zingiberaceae family and it is found growing in many places throughout Southeast Asia. Although it has a pungent odour, it is regarded as a delicacy by the Kadasan Dusun people in Sabah, Malaysia. The inner stem and its florescence are eaten and the whole plant is regarded to have importance in traditional medicine. Due to its importance to the local community, this research was conducted to study its chemical conposition and biological potentials. Plant materials were collected from six different locations in Sabah; Ranau (ECl), Sandakan (EC2), Danum (EC3), Ulu Kimanis (EC4), Paitan (ECS) and Long Pasia (EC6). Yield of essential oil and crude extract of all samples were in the following range: 22.33% "' 30.50%, of its fresh weight; 7.29% "' 14.61 %, of its dry weight. Both extracts were tested for antimicrobial, antioxidant activity and total phenolic content. It was evident that extracts with antimicrobial potential had no antioxidant activity, while extracts with high antioxidant and phenolic content exhibited weak antimicrobial activity. The essential oils of all specimens showed inhibition (10-67 %) against tested microbes except against BaCJllus sp., Salmonella typhi, Salmonella typhymurium and Listeria monocytogenes. On the other hand, crude ethanol extracts only exhibited moderate and weak activity against C/ostridium cellobioparum, Pseudomonas aurelis, Proteus mirabilis, Escherichia coli, Salmonella enteritidis, Staphylococcus aereus, Vibrio cholera, and Crytococcus neoformans. The ethanol extract from ECl showed high phenolic, free radical scavenging activity, ferric reducing antioxidant power and inhibition of linoleic acid peroxidation as compared to other extracts. Phenolic content and free radical scavenging activity were strongly correlated (r=0.863) and it might be the major contributor to the antioxidant activity of this species. This is the first report of the volatile chemical constituents of £ coccinea essential oil. In this investigation, inner stems of £ coccinea of six different populations were distilled and the essential oils were subjected to GC-MS analysis. A total of 21 types of volatile compounds were identified in the course of this investigation. The major volatile compounds in five specimens (ECl, EC2, EC4, ECS and EC6) of £ coccinea essential oils were linalool and citronellyl propionate. As for specimen EC3, its major compounds were dodecanal and linalool. The crude ethanol extract of £ coccinea had been profiled by using thin layer chromatograph. It was found that TLC fingerprinting of all the compounds appear at the same Rf value and can be assumed that all the crude ethanol extracts of £ coccinea collected from six different populations possessed compounds of similar retention factor. However, further analysis is needed to find out the bioactive compounds responsible for the bioactive potential in this particular species.